Development of the autoinflammatory disease damage index (ADDI). Issue 5 (3rd November 2016) - ter Haar, Nienke M; Annink, Kim V; Al-Mayouf, Sulaiman M; Amaryan, Gayane; Anton, Jordi; Barron, Karyl S; Benseler, Susanne M; Brogan, Paul A; Cantarini, Luca; Cattalini, Marco; Cochino, Alexis-Virgil; De Benedetti, Fabrizio; et al.
Abstract : Objectives: Autoinflammatory diseases cause systemic inflammation that can result in damage to multiple organs. A validated instrument is essential to quantify damage in individual patients and to compare disease outcomes in clinical studies. Currently, there is no such tool. Our objective was to develop a common autoinflammatory disease damage index (ADDI) for familial Mediterranean fever, cryopyrin-associated periodic syndromes, tumour necrosis factor receptor-associated periodic fever syndrome and mevalonate kinase deficiency. Methods: We developed the ADDI by consensus building. The top 40 enrollers of patients in the Eurofever Registry and 9 experts from the Americas participated in multiple rounds of online surveys to select items and definitions. Further, 22 (parents of) patients rated damage items and suggested new items. A consensus meeting was held to refine the items and definitions, which were then formally weighted in a scoring system derived using decision-making software, known as 1000minds. Results: More than 80% of the experts and patients completed the online surveys. The preliminary ADDI contains 18 items, categorised in the following eight organ systems: reproductive, renal/amyloidosis, developmental, serosal, neurological, ears, ocular and musculoskeletal damage. The categories renal/amyloidosis and neurological damage were assigned the highest number of points, serosal damage the lowest number of points. The involvement of (parents of) patients resulted in the inclusion of, for example, chronic musculoskeletal pain. Conclusions: An instrument to measure damage caused by autoinflammatory diseases is developed based on consensus building. Patients fulfilled a significant role in this process.